(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Summary 90 years XX c.took a deep and significant place in all sectors of social life. These years have brought profound changes in the spiritual sector of society, including the religions and religious culture . Circumstances surrounding the formation of new social, cultural and political development , changes in the ideological sphere , the development of national thinking and the development of spiritual national values life are critical factors the role of religion in social and political life. Update religions renaissance tend countries post atheistic society. Because for many years the country of national and spiritual values , no doubt, set the goal to return to their homes of origin. Development of religious thinking together with the strengthening of the position of traditional religious associations are allocated to Kazakhstan with the advent of the unknown , new destructive and nontraditional religious organization. The purpose of this article considers particular nontraditional religious teachings of Islamic schools in Kazakhstan as well as reveal the positions of non-traditional areas , to assess their impact in the national uniqueness. The theme of religion - it is a complex and sensitive issue . Religion should not be the basis of differences, and the basis of unity and harmony . We hope that the new enacted law of» religious activity and religious associations « to increase the effectiveness of secular policy in the religious sector , and more precisely clarify the secular principle. Opening preparatory training centers in « religion studies» in the central and eastern , west region our country would be possible to solve the problems of staffing shortages . For young people studying at religious centers should be taught subjects such as : religion and society, religion and law, religion and national spirit and the basis of secular morality. Youth , enthusiastic religion first need to educate the basis of national spirit and secular state, teach the graceful nature of Islam and humane values, hold positions in the minds how to love their homeland , honor society and people. We must teach the youth to religious ethical life, and from time to teach the basis of religion. Should pay attention to the direction of professional work among youth and to improve cultural and sports complexes in monocities . Key words: tolerance,national identity,religious renascent,religiousness,traditional religion ,values of islam, nontraditional religious,interconfessional dialogue,spiritual security, national tradition.